Student Role Supports for Younger and Older Middle- Aged Women: Application of a Life Event Model - Thacker, Charlene; Novak, Mark (Canadian Journal of Higher Education, 1991)
This paper is a report on a study of 276 women aged 35 to 64 who have re-entered university. We used the life-event framework to focus on the stress of university life, on the methods these women use to cope with stress and on their adaptations to the demands of school. We compared the re-entry experience of two sub-groups in our population: students aged 35 to 44 (with young families) and those aged 45 to 64 (with mature families). We found that each group had different motives for attending school, each group felt different strains during the school year and each group used different methods and resources to cope with the demands of student life. The paper concludes with a review of the literature on programs that meet the needs of re-entry women. We note the applicability of these programs to the distinct needs of younger and older re-entry women and we encourage the development of more programs to meet both groups' needs.